Vivências de prazer-sofrimento de professores que atuam em Educação Inclusiva - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
This dissertation focuses on the pleasure-pain of teachers who work with inclusive education in the city of Manaus. Aiming to understand the general pleasure-suffering teachers who work with inclusive education in Manaus from the analysis of the psychodynamic processes work. And the specific objectives of the research were: to characterize the organization of the work of teachers who work in inclusive education; recognize the suffering in the work; aggravating the distress signal, defense strategies and possible pathologies of work; identify the subjective mobilization and factors that contribute to the transformation of suffering; contribute to a reflection on the work in the context of inclusive education. We used a qualitative methodology, according to the theoretical contributions of psychodynamic work in that listening and preparation leads to a mobilization of change and transformation. Participants who composed the study were twenty-five teachers who work with inclusive education in the education system of municipal Manaus. Of the total, five are men and twenty women are. The research was conducted in a classroom of a public school located in the central-west of Manaus. Workshops were held listening clinic suffering, grounded in psychodynamic theory work, which was proposed in the discussion of subjective experiences at work. The speech was shared in the collective of workers and listening was based on the experiences of work. It was used as an instrument recorder and data sessions were transcribed and adopted the systematic analysis of Grounded Theory - ATF (GroundedTheory), adapted by Moraes (2010), using it specifically as technical analysis. The speeches were organized in the following lines of analysis: Work organization and work process; aggravating the suffering, signs and symptoms of illness; Processes subversion of suffering: subjective mobilization, cooperation and recognition. The categories were compared, leading to the axes of analysis, combining the data with the theoretical. From this study, it was concluded that the lack of a space for discussion configured the initial complaint from teachers and from the meetings was favored the formation of a collective in the sense of belonging was built. The study highlighted the contradictions between prescribed work and real, especially when dealing with the law of the process of inclusive education and the practice of this teacher to receive a disabled child. Since there are favorable conditions to carry out the work and the lack of limitation is one of the main guiding this work. It can be inferred that there was a transformation process in speech and action of these teachers. From the meetings and the possibility of discussions among teachers, there was a transformation of this positioning towards a joint responsibility, an identification in order to assume the inclusion as an action in your doing from the mobilization and cooperation. Thus, it was possible to understand the relationships between employee and the organization of work, as well as mediations and actions of those in favor of change in work. Thus, this study contributed to knowledge of how this transformation occurs subject and how the work is mobilizing to do this.
Keywords: Psicodinâmica do Trabalho; Oficinas de Clínica do Trabalho; Educação Inclusiva; Professores; Youth; Psychodynamics of Work; Labor Workshops Clinic; Inclusive Education; Teachers; CIÊNCIAS HUMANAS: SOCIOLOGIA